Synergistically enhanced electrical transport properties of SrTiO3via Fermi level regulation and modulation doping. Issue 37 (28th March 2022) - Li, Dongmei; Wang, Dongyang; Zhang, Xiao; Zhao, Li-Dong
Abstract : The thermoelectric performance of the insulator SrTiO3 was improved through synergistically enhanced electrical transport properties via Fermi level regulation and modulation doping. Abstract : SrTiO3 has gained wide attention as an oxide thermoelectric material due to its high Seebeck coefficient and excellent high-temperature thermal stability. However, its intrinsic insulatory properties hinder its development as a thermoelectric material. Herein, we synergistically improved the electrical transport properties of SrTiO3 by increasing carrier concentration and maintaining high carrier mobility via Fermi level regulation and modulation doping through co-doping and compositing. Nb and La co-doping notably heightened the carrier concentration and regulated the Fermi level in the conduction band, resulting in an enhanced ZT value from that of an insulator in SrTiO3 to 0.033 in Sr0.875 La0.125 Ti0.85 Nb0.15 O3 at 923 K. The subsequent TiB2 compositing simultaneously improved carrier concentration (4.82 × 10 17 cm 3 ) and afforded high carrier mobility (3.55 × 10 4 cm 2 V −1 S −1 ) in the Sr0.875 La0.125 Ti0.85 Nb0.15 O3 + 4% TiB2 sample at 923 K. The combination of synergistically improved carrier concentration and retained high carrier mobility resulted in an enhanced power factor (11.04 μW cm −1 K −2 at 923 K), maximum ZT (0.23 at 923 K) and average ZT (0.15 at 473–923 K) in Sr0.875 La0.125 Ti0.85 Nb0.15 O3 + 4% TiB2 through co-doping and compositing, which matches those of many excellent SrTiO3 -based materials. Our study demonstrated that the thermoelectric properties of SrTiO3 could be improved via synergistically enhanced electrical transport properties through Fermi level regulation and modulation doping via co-doping and compositing, which will inspire further research on SrTiO3 and other oxide thermoelectric materials with mediocre electrical transport properties.